Radikalisme Atau Tasamuh: Analisis Terhadap Ayat-Ayat Al-Qur’an Tentang Ahli Kitab - Muhammad Arsad Nasution (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
This paper describes the verses of the Qur'an relating to Ahl al-Kitab to see the contents of the verses with the interpretation approach. Broadly speaking, the verses of ahl al-kitab are related to the prohibition on choosing ahl al-kitab as the leader, relating to their attitude of dishonesty towards Muslims if they do not convert to their religion, and the mu'amalah relationship between Muslims and ahl al-kitab . The study of these verses shows that these verses do not give a negative tendency towards them but there are things that according to Allah Almighty must be more careful in giving attitude to them, such as the prohibition of choosing non-Muslims as leaders, does not mean the Ummah Islam is allowed to hate them, but they must be respected as creatures of Allah. The prohibition on choosing non-Muslims as leaders is only the political rights of the people which Allah SWT legalizes through his word. Some other verses show the permission to bermu'amalah with them. Therefore these verses describe the relationship of mutual respect for fellow believers. Interpretation between these verses laid the foundation of tasamuh (tolerance) between Muslims and scribes not leading to a radical understanding.